A Control Method of High Impact Energy and Cosimulation in Powder High-Velocity Compaction - Dongdong You; Dehui Liu; Hangjian Guan; Qingyun Huang; Zhiyu Xiao; Chao Yang (Advances in Materials Science and Engineering)
To enhance the impact energy of powder high-velocity compaction (HVC) and thus improve the green density and mechanical properties of the resulting compacts, a mechanical energy storage method using combination disc springs is proposed. The high impact energy is achieved by modifying existing equipment, and the hydraulic control system is developed to implement the automatic control of the energy produced from the disc springs. An interdisciplinary cosimulation platform is established using the ADAMS, AMESim, and LabVIEW software packages to perform the interactive control of the simulation process and the real-time feedback of the simulation results. A mechanical-hydraulic cosimulation of the energy control virtual prototype of the testing machine is conducted using this platform. The influence of the impact energy on the green density is studied according to the HVC experimental results of the iron-based powders, and then, the green compact with the higher relative density is produced. The experimental results indicate that the energy enhancement method using the combination disc springs is reasonable and that the hydraulic control scheme is reliable.